7. SOME FACTORS RELATED TO THE PATIENT SAFETY CULTURE OF HEALTH WORKERS AT KIEN GIANG GENERAL HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
Background: Patient safety prevents errors that may endanger the patient during care and treatment.Establishing a culture of patient safety in medical practice is important to improve the professionalenvironment and the quality of medical service.Objective: Analyzing some factors related to the patient safety culture of health workers at KienGiang general hospital, 2021.Methods: A cross-sectional study, quantitative research.Results: The study collected quantitative information from 950 health workers at Kien Giang generalhospital through questionnaires. The research results show differences in health workers’ patientsafety culture according to factors such as occupational title and patient contact (p
Keywords: Patient safety culture, Health workers, Related factors.